2018
DOI: 10.7748/ns.2018.e10693
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of high-fidelity simulation training to enhance clinical skills

Abstract: The use of interprofessional simulation training to enhance nursing students' performance of technical and non-technical clinical skills is becoming increasingly common. Simulation training can involve the use of role play, virtual reality or patient simulator manikins to replicate clinical scenarios and assess the nursing student's ability to, for example, undertake clinical observations or work as part of a team. Simulation training enables nursing students to practise clinical skills in a safe environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…This finding was in line with Kirkham’s research, in which he claimed that training provided through scenario simulation had many benefits. These benefits included allowing trainees to practice skills in a regulated environment, becoming aware of the consequences of their actions, developing their cognitive skills, building their decision-making processes, ensuring effective communication, and self-correcting based on immediate feedback from the instructor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with Kirkham’s research, in which he claimed that training provided through scenario simulation had many benefits. These benefits included allowing trainees to practice skills in a regulated environment, becoming aware of the consequences of their actions, developing their cognitive skills, building their decision-making processes, ensuring effective communication, and self-correcting based on immediate feedback from the instructor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca gereksiz yere tekrarlanan vajinal muayenelerin kadın tarafında travmatik olarak algılanması nedeniyle (24) etik olarak da uygun değildir. Bu çalışmaya benzer şekilde simülasyon eğitiminin hem öğrenciler hem de hastalar için güvenli bir ortamda klinik becerilerini geliştirme fırsatı sunduğu belirtilmektedir (1,3,8,25,26). Simülatör sayesinde ebelik öğrencilerinin vaginal muayeneyi en iyi şekilde öğrenmelerini sağlayabildiği bildirilmektedir (27).…”
Section: Discussionunclassified
“…[7] As a result, the advantages to utilize simulation are numerous as it may decrease anxiety in clinical performance, and meet teamwork competencies for students. [3,[6][7][8][9][10] A study by Waznonis (2015) also found that simulation offers the opportunity to increase self-confidence in students. [11] Previous studies are limited as they did not reflect on the working dynamics of simulation debriefing and its effects on decreasing anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2] It has been shown that simulation allows one to build self-confidence and develop competencies to help enable performance in a real-world setting. [3] Simulation has been defined by other authors as an approach which allows an individual to not only acquire and employ the competencies to create real-life situations, but also receive feedback to help enhance their academic needs. [4] Utilizing simulation allows students to increase their participation in learning activities.…”
Section: Introductionmentioning
confidence: 99%